Establishment of microcosm biofilm models that reproduce a cariogenic diet intake - Florez Salamanca, Elkin Jahir [UNESP]; Dantas, Rayssa Mariana [UNESP]; Rodriguez, Martha Juliana; Klein, Marlise Inêz [UNESP] (Taylor & Francis, 2020)
Biofilms were developed from human saliva on bovine enamel discs in four experimental conditions to investigate dental caries development: feast and famine (M1), abundance and scarcity (M2), three meals daily (M3), and three meals plus two snacks daily (M4). The main difference between these models was the diet for microbial growth. The evaluations included verifying the pH of the spent culture media and analyzing the enamel discs for demineralization (microhardness and roughness) and biofilms (biomass, viable populations of mutans streptococci, and total microbiota). Two major behaviors were observed: M1 and M2 promoted an acidic environment, while M3 and M4 maintained pH values closer to neutral. The demineralization process was slower in the neutral groups but more pronounced in M3, while a greater increase in microbiota and biomass was observed over time for both neutral groups. Thus, the M3 model was better at mimicking the oral environment that leads to demineralization.
Keywords: biofilms; Dental caries; mutans streptococci; saliva; tooth demineralization